Wujudkan Senyum Ceria Dan Gigi Sehat Melalui Edukasi Kesehatan Gigi Dan Mulut Pada Remaja - Alfah, Siti; AR, Aisyah; Qalbi, Astri Annur; Aminuddin, Andi Muhammad Adam; Feblina, Ayu Rahayu; Eni, St. Nur; Nurhaerani, Nurhaerani (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Dental and oral health as part of the body's health plays a role in determining a person's health status, but adolescents lack knowledge and awareness of dental and oral health. Objective: To increase adolescent knowledge about maintaining dental and oral health. The activity was carried out in Bilalang Village, Gowa Regency, and was attended by 24 adolescents consisting of 14 female adolescents and 10 male adolescents. Method: Conducting dental health education with material on maintaining dental and oral health in adolescents, questions and answers about dental and oral health in adolescents. Results: There was an increase in participant understanding after being given education. Before the activity, most adolescents did not know the importance of maintaining dental health. After the education, participants were able to provide examples and ways to clean their teeth and mouths properly. This activity proves that dental health education has an important role in shaping healthy behaviors in adolescents. Conclusion: A series of community service activities with the theme "Realizing Cheerful Smiles and Healthy Teeth Through Dental and Oral Health Education in Adolescents" has been well implemented, and there has been an increase in adolescent knowledge about dental health.